Large Metastatic Cardiac Tumor from Ascending Colon Cancer with Autopsy - Takashi Tomiyama; Takuya Shijimaya; Yasuki Sano; Sanshiro Kobayashi; Toshiro Fukui; Mitsuaki Ishida; Makoto Naganuma (Case Reports in Gastroenterology, 2021)
A metastatic cardiac tumor from colon cancer is an exceedingly rare clinical feature associated with a poor prognosis without therapeutic intervention; however, such cases may be frequently encountered in clinical practice, especially among the elderly. We report a case of synchronous double cancer of the prostate and ascending colon with metastases to multiple organs, including a large cardiac tumor. A 71-year-old Japanese man had prostate cancer with neck and para-aortic metastasis. He visited our hospital with complaints of fatigue and a positive fecal occult blood test result. Colonoscopy findings revealed the presence of a tumor in the ascending colon, and contrast-enhanced CT revealed a tumor in the heart, which was possibly due to metastasis from the ascending colon. The patient received palliative care and declined anticancer treatment. He died due to respiratory failure 3 months after the first diagnosis but did not show critical arrhythmia until death. Autopsy revealed the presence of a large mass in the right ventricle with tumor embolism of the right coronary artery. The cardiac mass was pathologically consistent with metastasis from the colon. In case of colorectal cancer with cardiac metastasis involving poor prognosis or performance status, best supportive care without any therapeutic intervention could be the optimal treatment for the quality of the remaining time.